Fatigue life analysis of an aircraft brake component to prevent damage and ensure operational safety. (November 2021) - Korba, Peter; Huňady, Róbert; Hovanec, Michal; Rácek, Branislav; Pavelka, Peter
Highlights: The fatigue analysis of two brake discs used in civil transport aircraft. Abstract: Safety is critical at all stages of aircraft operations, from air missions to ground operations. One of the most important airframe systems that affects ground safety efficiency is the wheel brake system. The brake is used to brake the aircraft from the moment the wheels touch the ground. During braking, the brake components are exposed to high temperatures and high dynamic stresses, which affect their wear and service life. The brakes of heavy aircraft are especially prone to overheating during landing and taxiing on the ground. The paper deals with fatigue analysis of two brake discs used in civil transport aircraft for short and medium haul. The aim of the study is to assess which variant reduces the risk of brake overheating problems and thus contributes to increased operational safety. In the paper, the principle of operation of a multiple-disc aircraft brake is thoroughly explained, including the loading conditions and the causes of disc failures. Geometric CAD models of discs were obtained by reverse engineering methods and the lifetime analysis was performed numerically using the finite element method.